Examining climate-related indices and landscape connectivity to understand mangrove fragmentation in Campeche, Mexico - Wiktor Halecki; Dawid Bedla; Nuria Hernández; Vincente Hernández (Landscape Online)
Megadiverse countries such as Mexico face significant challenges in safeguarding their ecosystems and species due to environmental and anthropogenic changes. Coastal biodiversity in the Gulf of Mexico, particularly within mangrove ecosystems, is especially vulnerable yet critical for understanding the impacts of global climate change. This study aims to evaluate the factors contributing to the ongoing chronic changes in and around mangroves. We focused on the Yucatán Peninsula in the western Caribbean Sea, utilizing satellite images from 1981 to 2020 to analyze decadal variations in mangrove coverage. Our findings revealed a high ecological index score of 0.71, underscoring the area’s considerable natural value, alongside an anthropogenic index score of 0.46, which highlights the significant impact of human activities. To enhance biodiversity connectivity and preservation, we propose a GIS- based spatial biological corridor technique, establishing protection zones. Urgent action is needed to promote improved forest management and restoration efforts, facilitating climate change adaptation for mangrove and adjacent ecosystems.